Descriptive Epidemiology of Paralympic Sports Injuries. Issue 8 (16th August 2014) - Webborn, Nick; Emery, Carolyn
Abstract: Paralympic sports have seen an exponential increase in participation since 16 patients took part in the first Stoke Mandeville Games on the opening day of the 1948 London Olympic Games. More than 4, 000 athletes took part in the London 2012 Paralympic Games. Few sporting events have seen such rapid evolution. This rapid pace of change also has meant challenges for understanding the injury risks of participation, not only because of the variety of sports, impairment types, the evolution of adapted equipment but also because of the inclusion of additional impairment types and development of new sports over time. Early studies were limited in scope but patterns of injuries are slowly emerging within Winter and Summer Paralympic sports. The IPC's London 2012 study is the largest to date with a prospective cohort study involving 49, 910 athlete‐days. The results identified large differences across sports and highlighted the need for longitudinal sport specific studies rather than solely games‐time studies. This will require collaboration with international sports federations to examine injury patterns and risk factors for injury in this population to appropriately inform injury prevention strategies. Further studies will also need to address the impact of sporting participation, injury, and future health.